PENGARUH KUALITAS PELAYANAN DAN KEPUASAN TERHADAP LOYALITAS ANGGOTA KOPERASI MEKAR SURYA KABUPATEN KARANGANYAR - Syarifudin, Novita Arman; Pujiani, Dewi (Surakarta Management Journal, 2021)
This study aims to determine the effect of service quality and satisfaction on member loyalty in the Mekar Surya Cooperative, Karanganyar Regency. The population in this study amounted to 253 members of the Mekar Surya Cooperative, Karanganyar Regency recorded in December 2020. The sampling technique in this study used a proportional random sampling technique, the sample was taken by 25% of the population, namely 59 respondents who met the sample selection criteria. The data analysis technique used in this research is multiple linear regression test and hypothesis testing using t-statistics and F- statistics with a significance level of 5%. The results show that the service quality variable partially affects member loyalty with a value of 3.740 which is greater than the t-table value of 2.003 with a significance of 0.000 and the satisfaction variable partially also affects member loyalty with a value of 5.749 greater than the t-table value. 2,003 with a significance of 0.000 as well. Service quality and satisfaction variables simultaneously affect member loyalty with a calculated F value of 75.150 and this is greater than F table 3.15 and a significant value of 0.000 <0.05.       This study aims to determine the effect of service quality and satisfaction on member loyalty in the Mekar Surya Cooperative, Karanganyar Regency. The population in this study amounted to 253 members of the Mekar Surya Cooperative, Karanganyar Regency recorded in December 2020. The sampling technique in this study used a proportional random sampling technique, the sample was taken by 25% of the population, namely 59 respondents who met the sample selection criteria. The data analysis technique used in this research is multiple linear regression test and hypothesis testing using t-statistics and F- statistics with a significance level of 5%. The results show that the service quality variable partially affects member loyalty with a value of 3.740 which is greater than the t-table value of 2.003 with a significance of 0.000 and the satisfaction variable partially also affects member loyalty with a value of 5.749 greater than the t-table value. 2,003 with a significance of 0.000 as well. Service quality and satisfaction variables simultaneously affect member loyalty with a calculated F value of 75.150 and this is greater than F table 3.15 and a significant value of 0.000 <0.05.